Jiawei Qifuyin Enhances Immunity and Improves Cognitive Impairment in APP/PS1 Mice Through Modulation of Neuroinflammatory Pathways - Cheng J; Li W; Wang L; Gao Y; Ma Y; Zhou M; Yang T; Yue C; Yan L; Lyu Y (Dove Medical Press, 2024)
Jiahua Cheng,1,* Wujuan Li,1,* Lanlin Wang,1,* Yu Gao,1 Yueran Ma,1 Min Zhou,1 Tian Yang,1 Changwu Yue,1,2 Long Yan,3 Yuhong Lyu1,2 1Yan'an Key Laboratory of Microbial Drug Innovation and Transformation, School of Basic Medicine, Yan'an University, Yan'an, Shaanxi, People's Republic of China; 2Shaanxi Engineering and Technological Research Center for Conversation and Utilization of Regional Biological Resources, Yan'an University, Yan'an, Shaanxi, People's Republic of China; 3Medical Imaging Center, Yan'an Traditional Chinese Medicine Hospital, Yan'an, Shaanxi, People's Republic of China*These authors contributed equally to this workCorrespondence: Long Yan; Yuhong Lyu, Email yanlong840212@163.com; yuhonglyu@126.comPurpose: To explore the protective effects and mechanisms of Jiawei Qifuyin on APP/PS1 mice, a model for Alzheimer's disease (AD).Methods: Network pharmacology tools were used to predict anti-AD targets and signaling pathways affected by Jiawei Qifuyin. In vitro studies assessed antioxidant and oxygen radical scavenging abilities, immune cell proliferation, and inflammatory cytokine levels in lipopolysaccharide-induced BV2 microglial cells. Cognitive ability in APP/PS1 mice was evaluated using the Morris Water Maze test. mRNA expression of neuroinflammatory factors, changes in intestinal microbiota, and short-chain fatty acid content were analyzed post-treatment.Results: Network pharmacology predicted that Jiawei Qifuyin affects AKT1, TNF-α, and AGE/RAGE pathways. It showed concentration-dependent antioxidant effects and modulated immune cell proliferation. IL-2, IL-6, and TNF-α levels in LPS-induced BV2 cells were significantly reduced. Treated animals exhibited improved cognitive performance, decreased brain amyloid-beta levels, and downregulated expression of IL-1β, IL-6, RAGE, and NF-κB. Significant changes in intestinal microbiota composition and SCFA content were observed.Conclusion: Jiawei Qifuyin may enhance immunity and improve cognitive impairment in APP/PS1 mice through regulation of inflammatory factors, gut microbiota, and the gut-brain axis.Keywords: Alzheimer's disease, Jiawei Qifuyin, neuroinflammation, intestinal microbiota, short chain fatty acid